Core/Shell Metal Halide Perovskite Nanocrystals for Optoelectronic Applications. (3rd March 2021) - Zhang, Chengxi; Chen, Jiayi; Kong, Lingmei; Wang, Lin; Wang, Sheng; Chen, Wei; Mao, Rundong; Turyanska, Lyudmila; Jia, Guohua; Yang, Xuyong
Abstract: Core/shell structured metal halide perovskite nanocrystals (NCs) are emerging as a type of material with remarkable optical and electronic properties. Research into this field has been developing and expanding rapidly in recent years, with significant advances in the studies of the shell growth mechanism and in understanding of properties of these materials. Significant enhancement of both the stability and the optical performance of core/shell perovskite NCs are of particular importance for their applications in optoelectronic technologies. In this review, the recent advances in core/shell structured perovskite NCs are summarized. The band structures and configurations of core/shell perovskite NCs are elaborated, the shell classification and shell engineering approaches, such as perovskites and their derivative shells, semiconductor shell, oxide shell, polymer shell, etc. are reviewed, and the shell growth mechanisms are discussed. The prospective of these NCs in lighting and displays, solar cells, photodetectors, and other devices is discussed in the light of current knowledge, remaining challenges, and future opportunities. Abstract : Core/shell metal halide perovskite nanocrystals show enhanced stability and optical properties, which are beneficial for their applications in lighting and displays, solar cells, photodetectors, lasing, photocatalysis, and biomedical imaging. In this review, recent advances in synthetic strategies and shell growth of core/shell nanocrystals are reviewed, and their enhanced material properties and emerging applications are discussed.